(untitled) (Ukrainian Journal of Ophthalmology, 2026)
International Scientific Conference “Filatov Memorial Lectures-2017” was held in Odessa on the 21st -22nd of May 2015. This huge national event in the field of health care presented scientific and practical program of immediate interest that included scientific sessions, lectures, discussions, and a specialized exhibition. The conference was a chance for scientists, researches, ophthalmology practitioners, and related specialists (neonatologists, radiologists, chemotherapeutist, pharmacologists, and biologists) to share their best practice, to improve professional skills, and to expand occupational contacts.